Copper coordination polymers with selective hole conductivity. Issue 17 (30th March 2022) - Michaels, Hannes; Golomb, Matthias J.; Kim, Byeong Jo; Edvinsson, Tomas; Cucinotta, Fabio; Waddell, Paul G.; Probert, Michael R.; Konezny, Steven J.; Boschloo, Gerrit; Walsh, Aron; Freitag, Marina
Abstract : Low-dimensional copper coordination polymers represent an alternative, unprecedented class of charge transport materials, comprised of molecular building blocks. Abstract : Emerging technologies in solar energy will be critical in enabling worldwide society in overcoming the present energy challenges and reaching carbon net zero. Inefficient and unstable charge transport materials limit the current emerging energy conversion and storage technologies. Low-dimensional coordination polymers represent an alternative, unprecedented class of charge transport materials, comprised of molecular building blocks. Here, we provide a comprehensive study of mixed-valence coordination polymers from an analysis of the charge transport mechanism to their implementation as hole-conducting layers. Cu II dithiocarbamate complexes afford morphology control of 1D polymer chains linked by (CuI2X2 ) copper halide rhombi. Concerted theoretical and experimental efforts identified the charge transport mechanism in the transition to band-like transport with a modeled effective hole mass of 6 m e . The iodide-bridged coordination polymer showed an excellent conductivity of 1 mS cm −1 and a hole mobility of 5.8 10 −4 cm 2 (V s) −1 at room temperature. Nanosecond selective hole injection into coordination polymer thin films was captured by nanosecond photoluminescence of halide perovskite films. Coordination polymers constitute a sustainable, tunable alternative to the current standard of heavily doped organic hole conductors.